Bioconversion of food waste into biogas and fertilizer : a focus study on acidogenic reactor operation - Tan, Yu Hong. (2010)
The main goal of the demonstration project was to provide an opportunity for the study team to gain experience on the setting up and operation of the pilot-scale food waste to biogas and fertilizer plant in order to ultimately build the industrial-scale HASL systems for commercialization if the trial is demonstrated successful. During the project duration, the project team conducted various tasks to investigate what is the most optimum operating conditions of the system as the optimized operation would result in (1) less capital cost in reactor construction and land requisite for small size of reactors, (2) more revenue from treatment tariff because of high rate of biological conversion, (3) saving in manpower requirement and training due to process simplicity, and (4) faster and higher energy output resulting from high methane production rate in the following methanogenic reactors. Some effort was also put on the study of the effectiveness of T6 effluent inter-phase recirculation (dilution of T4 leachate fed to T6) and intra-phase recirculation (using T7 effluent as dilution water for T4 treatment). The recirculation of T6 effluent would save the chemical cost for pH neutralization and reduce the consumption of clean tap water in the operation. The effluent quality of several key processes/reactors in the pilot plant was also examined under different T4 leachate conditions. The original designed and installed aerobic processes (T7 to T10) in the pilot plant were good enough to biologically remove the residue organic compounds in the process water/effluent/wastewater after anaerobic digestion of T4 leachate in the T6. The final effluent from the pilot plant was also able to meet the discharge requirements stated in the Drainage and Sewage Act of PUB in the tested aspects such pH, COD, suspended solid, and alkalinity. In the report, sample calculation were shown in the Appendix to fine tune the aerobic processes such as both conventional activated sludge process and newly developed membrane bioreactor process. Overall speaking, this extended project successfully achieved its major objective to determine the optimal fermentation modes of raw food waste in the acidogenic reactors and gain experiences on the operation and maintenance of several proposed fermentation modes. The data obtained in this project will help the engineers to establish suitable design for the acidogenic reactors. The post treatment of the final effluent from the processes in the pilot plant was also satisfactory and met the key requirements of PUB sewage discharge act.